Glucose-lowering drugs or strategies, atherosclerotic cardiovascular events, and heart failure in people with or at risk of type 2 diabetes: an updated systematic review and meta-analysis of randomised cardiovascular outcome trials. Issue 5 (May 2020) - Ghosh-Swaby, Olivia R; Goodman, Shaun G; Leiter, Lawrence A; Cheng, Alice; Connelly, Kim A; Fitchett, David; Jüni, Peter; Farkouh, Michael E; Udell, Jacob A
Summary: Background: In our 2015 systematic review and meta-analysis of cardiovascular outcome trials for glucose-lowering drugs or strategies in people with or at risk of type 2 diabetes, we reported a modest reduction in atherosclerotic cardiovascular events and an increased risk of heart failure, but with heterogeneous effects by drug or intervention type. In view of the completion of many large cardiovascular outcome trials since our previous analysis, including trials of novel drugs that have shown beneficial effects on cardiovascular outcomes, we aimed to update our analysis to incorporate these findings. Methods: We did an updated systematic review and meta-analysis of large cardiovascular outcome trials of glucose-lowering drugs or strategies in people with or at risk of type 2 diabetes. We searched Ovid MEDLINE, PubMed, and the Cochrane Central Register of Controlled Trials databases for reports of trials published from Nov 15, 2013 to Nov 20, 2019. We included randomised controlled trials with a minimum of 1000 adults (aged ≥19 years) with or at risk of type 2 diabetes, with major adverse cardiovascular events (MACE) as an outcome, and with follow-up of at least 12 months. We excluded trials with patients enrolled with an acute cardiovascular event. The main outcomes of interest were MACE (generally defined as a composite of cardiovascular death, myocardial infarction, or stroke) and heart failure. We calculated pooled risk ratios (RRs) and 95% CIs with inverse-variance random-effects models, did meta-regression to analyse treatment effects per difference in bodyweight achieved, and explored results stratified by baseline subgroups. Findings: Our updated search yielded 30 eligible trials (n=225 305). The mean age of participants was 63·0 years (SD 8·4) and mean duration of diabetes was 9·4 years (6·6). After a mean follow-up of 3·8 years (1·8), 23 016 (10·2%) participants had MACE and 8169 (3·6%) had a heart failure event. Glucose-lowering drugs or strategies lowered the risk of MACE compared with standard care or placebo (RR 0·92, 95% CI 0·89–0·95, p<0·0001), with no overall effect on the risk of heart failure (0·98, 0·90–1·08, p=0·71). However, across drug classes or strategies, the magnitude and directionality of RR for heart failure varied (pinteraction <0·0001), with meta-regression showing that a decrease in bodyweight of 1 kg was associated with a 5·9% (3·9–8·0) relative decrease in the risk of heart failure (p<0·0001). Among trials that assessed drug classes or strategies associated with weight loss (intensive lifestyle changes, GLP-1 receptor agonists, or SGLT2 inhibitors), the risk reduction for MACE was consistent among participants with (0·87, 0·83–0·92) and without (0·92, 0·83–1·02) established cardiovascular disease at baseline (pinteraction =0·33). For heart failure, the RR for drug classes or strategies associated with weight loss was consistent among participants with (0·80, 0·73–0·89) and without (0·84, 0·74–0·95) cardiovascular disease at baseline (pinteraction =0·63). Interpretation: Glucose-lowering drugs or strategies overall reduced the risk of fatal and non-fatal atherosclerotic events. The effect on heart failure was neutral overall but varied substantially by intervention type, with interventions associated with weight loss showing a beneficial effect. The cardiovascular and heart failure benefits of interventions associated with weight loss might extend to patients without established cardiovascular disease. Funding: None.